Estriol‐mediated neuroprotection in multiple sclerosis localized by voxel‐based morphometry. Issue 9 (24th August 2018) - MacKenzie‐Graham, Allan; Brook, Jenny; Kurth, Florian; Itoh, Yuichiro; Meyer, Cassandra; Montag, Michael J.; Wang, He‐Jing; Elashoff, Robert; Voskuhl, Rhonda R.
Abstract: Introduction: Progressive gray matter (GM) atrophy is a hallmark of multiple sclerosis (MS). Cognitive impairment has been observed in 40%–70% of MS patients and has been linked to GM atrophy. In a phase 2 trial of estriol treatment in women with relapsing–remitting MS (RRMS), higher estriol levels correlated with greater improvement on the paced auditory serial addition test (PASAT) and imaging revealed sparing of localized GM in estriol‐treated compared to placebo‐treated patients. To better understand the significance of this GM sparing, the current study explored the relationships between the GM sparing and traditional MRI measures and clinical outcomes. Methods: Sixty‐two estriol‐ and forty‐nine placebo‐treated RRMS patients underwent clinical evaluations and brain MRI. Voxel‐based morphometry (VBM) was used to evaluate voxelwise GM sparing from high‐resolution T1‐weighted scans. Results: A region of treatment‐induced sparing (TIS) was defined as the areas where GM was spared in estriol‐ as compared to placebo‐treated groups, localized primarily within the frontal and parietal cortices. We observed that TIS volume was directly correlated with improvement on the PASAT. Next, a longitudinal cognitive disability‐specific atlas (DSA) was defined by correlating voxelwise GM volumes with PASAT scores, that is, areas where less GM correlated with less improvement in PASAT scores. Finally, overlap between the TIS and the longitudinal cognitive DSA revealed a specific region of cortical GM that was preserved in estriol‐treated subjects that was associated with better performance on the PASAT. Conclusions: Discovery of this region of overlap was biology driven, not based on an a priori structure of interest. It included the medial frontal cortex, an area previously implicated in problem solving and attention. These findings indicate that localized GM sparing during estriol treatment was associated with improvement in cognitive testing, suggesting a clinically relevant, disability‐specific biomarker for clinical trials of candidate neuroprotective treatments in MS. Abstract : We explored the relationship between the gray matter (GM) sparing and paced auditory serial addition test (PASAT) improvement in the context of traditional magnetic resonance imaging measures and other clinical outcomes in a recent phase 2 trial of estriol treatment in women with relapsing–remitting multiple sclerosis (MS). Using voxel‐based morphometry, we discovered a region of cortical GM in the medial frontal lobe that was both associated with PASAT performance and preserved with estriol treatment. These findings indicate that localized GM sparing during estriol treatment was associated with improvement in cognitive testing, suggesting a clinically relevant, disability‐specific biomarker for clinical trials of candidate neuroprotective treatments in MS.